Lawyers and legal culture in British North America : Beamish Murdoch of Halifax - Girard, Philip (Osgoode Society for Canadian Legal History series., 2011)
"From award-winning biographer Philip Girard, Lawyers and Legal Culture in British North America is the first history of the legal profession in Canada to emphasize its cross-provincial similarities and its deep roots in the colonial period. Girard details how nineteenth-century British North American lawyers created a distinctive Canadian template for the profession by combining the strong collective governance of the English tradition with the high degree of creativity and client responsiveness characteristic of U.S. lawyers - a mix that forms the basis of the legal profession in Canada today. Girard provides a unique window on the interconnections between lawyers' roles as community leaders and as legal professionals. Centred on one pre-Confederation lawyer whose career epitomizes the trends of his day, Beamish Murdoch (1800-1876), Lawyers and Legal Culture in British North America makes an important and compelling contribution to Canadian legal history."--Pub. desc.